The Role of Pitamaha in Balinese Artistic Transformation: A Comparison Between Kamasan and Gusti Nyoman Lempad Artistic Style - Wulandari, Anak Agung Ayu (Humaniora, 2016)
The Balinese artistic traditions of wayang style paintings that were known as Kamasan lasts for generations occurred some changes. Following the collapse of Balinese traditional court, the arrival of western artists and scholars, Pita Maha association was established to prevent the excess of commercialism to Balinese arts and crafts. A new generation of artists started to emerge, not only they adopted western painting techniques taught by their western ‘gurus’, but they also showed freedom of self-expressions in their works; one considered as a genius was Gusti Nyoman Lempad. The aim of this research was to compare the artistic transformation before Pita Maha and after Pita Maha. It was done by analyzing examples of Kamasan styled painting and works of Lempad through the qualitative method with a case study approach. The analyses show the differences between both styles regarding themes, iconographies, human figures proportions and composition, presentation of narrative stories, decorative elements and availability of artists’ signature in the paintings. It shows the artistic transformation of Balinese art. Through Pita Maha, Balinese starts to adopt western painting techniques, while preserving the cultural inheritance and symbolic value of traditional art in addition to their economic value.